Community mental health care after self-harm: A retrospective cohort study. (July 2017) - Spittal, Matthew J; Shand, Fiona; Christensen, Helen; Brophy, Lisa; Pirkis, Jane
Objective: Presentation to hospital after self-harm is an opportunity to treat underlying mental health problems. We aimed to describe the pattern of mental health contacts following hospital admission focusing on those with and without recent contact with community mental health services (connected and unconnected patients). Methods: We undertook a data linkage study of all individuals admitted as a general or psychiatric inpatient to hospital after self-harm in New South Wales, Australia, between 2005 and 2011. We identified the proportion of admissions where the patient received subsequent in-person community mental health care within 30 days of discharge and the factors associated with receipt of that care. Results: A total of 42, 353 individuals were admitted to hospital for self-harm. In 41% of admissions, the patient had contact with a community mental health service after discharge. Patients connected with community mental health services had 5.33 (95% confidence interval = [5.09, 5.59]) times higher odds of follow-up care than unconnected patients. Other factors, such as increasing age and treatment as a psychiatric inpatient, were associated with lower odds of follow-up community care. Conclusion: Our study suggests that full advantage is not being taken of the opportunity to provide comprehensive mental health care for people who self-harm once they have been discharged from the inpatient setting. This is particularly the case for those who have not previously received community mental health care. There appears to be scope for system-level improvement in the way in which those who are treated for self-harm are followed up in the community.